Determination of the Growth and Vitality Indicators of Mulber Tree Cuttings in the Climate Conditions of the Republic of Karakalpaкstan (Texas Journal of Agriculture and Biological Sciences, 2023)
The article examines the growth and viability of mulberry cuttings in the climatic conditions of the Republic of Karakalpakstan. The growth and viability indicators of the planted cuttings and the germination period of the experimentally planted cuttings were determined.